Salmonella, total coliform, faecal coliform, escherichia coll. investigation of well water in the vicinity of Badang, Kota Bharu - Azemi, Muhammad Fazlan (Universiti Sains Malaysia, 2016)
A study of Salmonella, total coliform, faecal coliform and Escherichia Coli in well water collected from 34 sampling points from seven areas in the vicinity of Badang, Kota Bharu was conducted. The area involved were Kampung Kijang, Kampung Che Latif, Kampung Semut Api, Kampung Badang, Kampung Pulau Pisang, Kampung Pulau Kundur and Kampung Dal. Well water was collected two times at each sampling point from March 2016 to April 2016. The objective of this study was to investigate the presence of Salmonella, total coliform, faecal coliform and Escherichia coli. Furthermore it was done to find the factors contributing their survival in well water. The laboratory testing of bacteria was conducted using membrane filtration technique and streak plate technique. The result of this study showed some of those bacteria were significantly correlated to four factors which were pH, dissolved oxygen, depth of well and distance of well from sanitary tank, at p < 0.05. In addition, the numbers of those bacteria was different between close well, partially close well and open well. Higher number of bacteria was found in close well. Overall, no Salmonella was found in the vicinity of Badang. The number of coliform bacteria in all area in the vicinity of Badang exceed the drinking water quality standard given out by Ministry of Health of Malaysia (0 CFU/100ml)